Kontribusi Guru PAI dalam Upaya Membimbing Ibadah Shalat Berjamaah pada siswa Kelas IV SDIT Insan Kamil Bukittinggi - Afsih, Mashitah Febri; Tamrin, Isnando; Rahmi, Ulva; Rahmi, Siska Yulia (Lembaga Yasin AlSys, 2024)
The teacher's contribution is very important in terms of worshiping students. PAI teachers have the responsibility to guide student behavior to achieve learning goals. As is the case in carrying out congregational prayers. The aim of this research is to determine the contribution of teachers in efforts to guide congregational prayers at SDIT Insan Kamil Bukittinggi. After conducting research, the following results were obtained; (1) The contribution of PAI teachers in efforts to guide congregational prayers for class IV students at SDIT Insan Kamil Bukittinggi is that PAI teachers carry out efforts to guide congregational prayers using several methods, namely, education by example, education by habituation, and education by advice. Among the contributions of these teachers include: PAI teachers as motivators, PAI teachers as role models (examples), PAI teachers as mentors (advisors), and PAI teachers as evaluators. (2) Supporting factors for PAI teachers in guiding congregational prayers are adequate worship facilities, a supportive environment and good cooperation between teachers, while (3) factors inhibiting student behavior, there is still a lack of awareness of the importance of congregational prayers and solutions provided by PAI teachers in overcoming inhibiting factors. provide supervision, guidance and discipline in the implementation of congregational prayers.